EFFECT OF SALINITY ON PIGMENT CONCENTRATIONS OF SOME TROPICAL PHYTOPLANKTERS - Bhattathiri, P M A; Devassy, V P (Indian Journal of Fisheries, 2011)
Estuaries are characterised by marked diurnal and seasonal changes insalinity. These changes are brought about either by the tidal variations or bythe infltix of freshwater from rivers and land runoff caused by the monsoonsystan. As a result, the organisms inhabitiing the estuaries have to adapt themsdvesto wide changes in salinity